Wavelets Analysis for Time Series - Christen, Alejandra (2019)
Wavelet analysis has been widely used to analyze time series and has countless applications in astronomy. Because of its characteristics it is a method that is well suited to approximate functions, eliminate noise, detect points of change, discontinuities and periodicities. In this article an introduction to the wavelet theory and its use in time series is presented. Numerical simulations and some real examples are developed in the software R.